Implementation of Educational Technology in the Development Area in Christian Religious Education in the Digital Age - Butar-butar, Imelda; Sitorus, Jim; Rantung, Dyoys Aneke; Boiliu, Noh Ibraihm (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Along with effort transformation in field education , technology education have very important role. In article this outlined about application technology education area development. For get inside data article this, done study descriptive qualitative with use method observation and interview to three lecturers Christian religious education and some students in the faculty psychology, faculty agriculture and faculty technique. From fifth area technology education, by special article this discuss application technology education area development in Christian religious education in the digital age concerns aspect technology print, audio visual technology, technology based computer and multimedia technology.